Pengaruh perubahan spasi nosel pada aliran dua fase terhadap kinerja liquid-gas ejector - Supandi Supandi; Edi Karyadi; Hadimi Hadimi (Universitas Muhammadiyah Metro, 2021)
Liquid-gas ejector is an energy conversion device capable of flowing air fluid by utilizing water fluid based on the pressure difference between the two fluids without using moving parts. This study aims to determine the effect of changing nozzle spacing on the two-phase flow on the performance of the liquid-gas ejector. The method used is to carry out an experiment whose stages include: determination of nozzle spacing parameters, primary flow rate, and secondary flow rate. Then perform tests on the liquid-gas ejector installation and collect data. The test was carried out by alternately varying the nozzle spacing, primary flow rate, and secondary flow rate. Then analyze the data that has been collected to get the efficiency or performance of the liquid-gas ejector from changes in nozzle spacing. Increasing the nozzle spacing causes a decrease in the efficiency of the liquid gas ejector. The efficiency of the liquid gas ejector with nozzle spacing 5, 10, 15, 20, and 25 mm is 17.17%, 13.49%, 12.06%, 11.41, respectively. %, and 10.47%.Keywords: Nozzle spacing, flow, two phases, performance, liquid-gas ejector.